2007
DOI: 10.1007/s10620-007-9864-7
|View full text |Cite
|
Sign up to set email alerts
|

Dilation of Benign Strictures in the Esophagus and Colon with the Polyflex Stent: A Case Series Study

Abstract: Polyflex, a new self-expanding plastic stent (SEPS), is increasingly used to treat obstructions in the gastrointestinal tract. The majority of reports on Polyflex come from tertiary referral centers. This retrospective study describes the efficacy and safety of this new SEPS for the treatment of benign strictures in esophagus and colon and its use in a community hospital. Seven patients were treated from August 2003 through December 2006. All of them presented with severe strictures, and were treated with Poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 18 publications
(15 reference statements)
1
26
0
Order By: Relevance
“…half of patients in 7 series, [48][49][50][51][52][53][54]56 and in almost two-thirds of procedures in the remaining series. 55 This high migration rate is likely the result of the fully covered stent design, the smooth outer surface of the stent, and the insufficient anchoring support provided by the stricture.…”
Section: Sepssmentioning
confidence: 95%
See 2 more Smart Citations
“…half of patients in 7 series, [48][49][50][51][52][53][54]56 and in almost two-thirds of procedures in the remaining series. 55 This high migration rate is likely the result of the fully covered stent design, the smooth outer surface of the stent, and the insufficient anchoring support provided by the stricture.…”
Section: Sepssmentioning
confidence: 95%
“…During the last 5 years, 8 studies have reported on more than 150 patients treated with a Polyflex stent for (refractory) benign esophageal strictures ( Table 2). [48][49][50][51][52][53][54][55][56] Indications for stent placement in these series included anastomotic strictures, followed by peptic strictures, caustic strictures, postradiation strictures, and some other causes.…”
Section: Sepssmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide range of endoscopic techniques have been used to treat postoperative colonic strictures, including mechanical dilation by means of expanding radial balloon dilators or fixed-diameter push-type dilators, electroincision or Nd-YAG laser stricturotomy in combination with balloon dilation [14][15][16], and more recently temporary insertion of self-expandable metal or plastic stents [17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…67 There are very limited data on the use of esophageal SEPSs for the management of colonic strictures. 68 In a report of 3 patients with benign postoperative strictures at the rectosigmoid junction or the sigmoid colon, the placement of esophageal SEPS yielded resolution of strictures and/or symptoms in all patients. In another report of 21 patients with benign colonic strictures, SEMS placement yielded clinical success in 76% with a complication rate of 42%, a majority of which occurred in patients with diverticular strictures.…”
Section: Colonic Stentsmentioning
confidence: 95%